2021
DOI: 10.9734/ajrid/2021/v8i330236
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Cycle Threshold (Ct) Value and IL-6 and D-Dimer in Chip-based RT-PCR Positive COVID-19 Cases: Study from a Stand-alone Laboratory

Abstract: Background: Novel Coronavirus (SARS-COV-2) is a leading cause of morbidity and mortality since the beginning of 2020 leading to range of symptoms from mild flu to respiratory distress, which is called COVID-19. RTPCR being the main diagnostic test can confirm the presence of the virus in the clinical samples, while various studies have defined Interleukin-6 and D-dimer as potent biomarker for severity. In this study, we have attempted to correlate the severity of COVID-19 with the presence of IL-6 and D-dimer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…However, Yuan et al found no such correlation [ 22 ]. Two more recent studies also failed to observe any correlation between the Ct value and D-dimer level [ 24 , 25 ]. Although neither study compared D-dimer values between subjects with different Ct values, the results of both studies support our findings showing significantly higher D-dimer values in subjects with low Ct values.…”
Section: Discussionmentioning
confidence: 99%
“…However, Yuan et al found no such correlation [ 22 ]. Two more recent studies also failed to observe any correlation between the Ct value and D-dimer level [ 24 , 25 ]. Although neither study compared D-dimer values between subjects with different Ct values, the results of both studies support our findings showing significantly higher D-dimer values in subjects with low Ct values.…”
Section: Discussionmentioning
confidence: 99%